ANALYSIS OF LEARNING DIFFICULTIES IN AN EDUCATIONAL INSTITUTION IN PORTO ALEGRE - Machado de Mello, Larissa (Revista Gênero e Interdisciplinaridade, 2023)
Learning difficulties have a lot of influence on the life of the child and family, due to the damage they cause in all areas of personal development. This article aims to investigate learning difficulties and teaching strategies applied by educators in a kindergarten located in the city of Porto Alegre/RS. Learning is strongly connected with the family environment, so that a better interaction occurs, there must be a partnership between the school, family and student. For the construction of the aforementioned research, a bibliographical analysis was carried out on the subject and observations of the school and the educator’s didactic work, where it was verified high levels of difficulties due to family and social causes and the teaching methodology.